Modelling for combat task allocation problem of aerial swarm and its solution using wolf pack algorithm. (2016) - Li, Hao; Xiao, Renbin; Wu, Husheng
To cope with the combat task allocation problems of aerial swarm, firstly, the assumption of battlefield environment was made. And the two multi-attribute principal parts of battlefield, swarm aerocraft (SA) and attacked target (AT) were analysed respectively. Secondly, based on comprehensive consideration of stealth and anti-stealth, attack and counter attack, multi-vehicle cooperation, etc., the objective function was established after analysing the costs and benefits that SA taking the task of reconnaissance, attack and assessment. Then, the task allocation model with the characteristics of multi-target, multi-task, multi-constraint, heterogeneous multi-aerocraft was established after considering some constrains, such as ammunition limit, etc. Based on binary wolf pack algorithm and a novel integer coding method which can better convey the information of the model, an integer coding wolf pack algorithm (ICWPA) was proposed to solve the task allocation model. The simulation results show that the model and the algorithm can effectively solve the combat task allocation problem of aerial swarm.